2008
DOI: 10.1007/s10649-008-9131-7
|View full text |Cite
|
Sign up to set email alerts
|

Exemplifying definitions: a case of a square

Abstract: In this study we utilize the notion of learner-generated examples, suggesting that examples generated by students mirror their understanding of particular mathematical concepts. In particular, we explore examples generated by a group of prospective secondary school teachers for a definition of a square. Our framework for analysis includes the categories of accessibility and correctness, richness, and generality. Results shed light on participants' understanding of what a mathematical definition should entail a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
27

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 9 publications
3
47
0
27
Order By: Relevance
“…Van Dormolen & Zaslavsky, 2003), students' beliefs about them (Zaslavsky & Shir, 2005), and students' guided collaborative development of definitions in contexts new to them (Larsen & Zandieh, 2008;Zandieh & Rasmussen, 2010). Studies have suggested that students who spontaneously generate examples in response to new definitions later perform better on tasks involving the defined concepts (Dahlberg & Housman, 1997), and there has been much recent discussion of the way in which example generation tasks might help students to modify their example spaces so that these more closely coincide with the extensions of the defined concepts (Mason, 2002;Watson & Mason, 2005;Zazkis, Liljedahl & Chernoff, 2008;Zazkis & Leikin, 2008). Definitions are also discussed in the extensive literature on proof, which focuses on the role of definitions as a deductive base in arguments about whole classes of objects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Van Dormolen & Zaslavsky, 2003), students' beliefs about them (Zaslavsky & Shir, 2005), and students' guided collaborative development of definitions in contexts new to them (Larsen & Zandieh, 2008;Zandieh & Rasmussen, 2010). Studies have suggested that students who spontaneously generate examples in response to new definitions later perform better on tasks involving the defined concepts (Dahlberg & Housman, 1997), and there has been much recent discussion of the way in which example generation tasks might help students to modify their example spaces so that these more closely coincide with the extensions of the defined concepts (Mason, 2002;Watson & Mason, 2005;Zazkis, Liljedahl & Chernoff, 2008;Zazkis & Leikin, 2008). Definitions are also discussed in the extensive literature on proof, which focuses on the role of definitions as a deductive base in arguments about whole classes of objects.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A special issue of this journal was recently dedicated to the role of examples in students' learning, and several articles in that issue discussed example generation (e.g., Watson and Shipman, 2008;Goldenberg and Mason, 2008;Zazkis and Leikin, 2008). Research in this area includes investigations into the richness and structure of students' example spaces (Goldenberg and Mason, 2008), the role of examples as pedagogical tools (Weber et al, 2008) and the pedagogical benefits of asking learners to generate their own examples of mathematical concepts (Watson and Mason, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The research data was analyzed by content analysis. The researchers considered the framework specified by Zazkis and Leiken (2008) and then expanded by Gokkurt (2014) in the identification process under categories and encodes of the data obtained defining derivatives, giving examples to derivatives, visualizing the definition of derivative and explaining the relationship between derivatives and continuity.…”
Section: Method(s)mentioning
confidence: 99%